REALITAS SOSIAL DALAM SENI POSTER SEBUAH KAJIAN KARYA POSTER SHEPARD FAIRY - Dwi Haryanto (Institut Seni Indonesia Yogyakarta, 2013)
A poster, briefly dominated the visual element that is able to seize the attention of the audience ratherthan the verbal element. However, in fact that would be submitted by a poster is